Systematic Literature Review: Ontologi Ilmu - Noprianti, Noprianti (Yayasan Sembilan Pemuda Indonesia, 2025)
Ontology is one of the studies of philosophy. As a branch of philosophy, ontology aims to investigate and abstract the nature of complete reality which is single, absolute and eternal. The study discusses the existence of something concrete. Ontology discusses reality or an entity for what it is. Discussing ontology means discussing the truth of a fact. To get that truth, ontology requires a process of how the reality can be recognized as true. This research uses the SRL (systematic literature review) method. Data collection is obtained from the results of data collection from similar previous studies. The journals obtained and used in this study were 15 National journals from the google sholar database. The results obtained in this study are that Ontology is a study of the nature of existence or reality, has a very close and fundamental relationship with various fields of science. Each discipline has a different ontology, reflecting fundamental assumptions about what they study and how they understand it.